1977
DOI: 10.1177/036354657700500302
|View full text |Cite
|
Sign up to set email alerts
|

Posterior shoulder lesions in throwing athletes

Abstract: Posterior shoulder lesions have terminated the careers of throwing athletes.We wish to present four case reports of posterior shoulder lesions which underwent operative intervention in an attempt to alleviate the individual's symptomatology and permit a return to throwing. The four cases are those of active professional baseball players whose careers were all but terminated due to intractable posterior shoulder symptoms during and after throwing. None of the individuals responded to multiple conservative regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 0 publications
2
46
0
1
Order By: Relevance
“…These were distinct from typical Bennett lesions as described by several authors [3,12,16] and we presumed they would cause painful abutment on the spur (Fig. 2).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…These were distinct from typical Bennett lesions as described by several authors [3,12,16] and we presumed they would cause painful abutment on the spur (Fig. 2).…”
Section: Introductionsupporting
confidence: 54%
“…We also noticed a posterior spur was common in throwing athletes. There had been reports of open resection of posterior ossifications in throwing athletes with unreproducible results [2,12,13,16]; however, Ozaki et al [16] reported an improvement in all parameters in a series of seven baseball pitchers and Meister et al [13] suggested 10 of 18 players returned to their previous level of throwing. In 1996, we thus decided to generalize the glenoidplasty in arthroscopic treatment of PGSI [10].…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses have been proposed regarding the mechanisms of this lesion, such as traction on the posterior joint capsule or triceps tendon during the follow-through phase of throwing, posterior impingement of the humeral head on the glenoid in the late-cocking phase, or a wringing action during the acceleration phase. [1][2][3]6,7 In addition, local irritation of the joint capsule and axillary nerve by the bony spur and internal impingement have been suggested as possible causes for how the bony spur induces posterior shoulder pain in throwing. [6][7][8] The pathologic significance of the Bennett lesion is still controversial, and which type of Bennett lesion induces throwing pain is not clear.…”
mentioning
confidence: 99%
“…Lombardo ve ark. [49] 1977'de, açık yaklaşımla tedavi ettikleri hastalarda posterior omuz kapsü-lü ve çevresi yumuşak dokulardaki fibrotik değişiklikleri göstermişlerdir. Andrews ve ark.…”
Section: İnternal Sikişma Sendromu (Iss)unclassified